Helping Distance Learners Stay Connected: The Effectiveness of Mobile Learning via SMS at Open University Malaysia - Lim , Tina Swee Kim; Zoraini Wati Abas; Mansor Fadzil (2011)
Distance learners often face what is known as transactional distances in terms of geographical, time, psychological and communication spaces (Moore, 1997). More often than not, compared to full time students, these adult learners who mostly hold full time jobs and have family commitments face a daunting task when it comes to juggling between studies, work and family. They often struggle to find that extra time and space to fit in their studies and frequently need to exert extra effort to ensure that they remain connected to the university, their tutors and their peers. This paper describes Open University Malaysia’s efforts in actively supporting learners in their studies through the use of text messaging technology, the simplest and most widely used of all mobile technology applications available. Further, it illustrates how mobile technology enhances the blended approach to instruction and lends more flexibility and ubiquity to the learning process. It also examines the effectiveness of the initiative in terms of helping learners to (1) review/locate/remember course facts easily, (2) discuss online, (3) manage their learning, (4) persevere in their studies, and (5) remember important dates and actions to be taken related to the course. Both quantitative and qualitative data are presented.(Abstract by authors)